2021
DOI: 10.3389/fmicb.2021.689855
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Rhizosphere Metagenome Reveals Newfound Potential Soil Zn-Mobilizing Bacteria Contributing to Cultivars’ Variation in Grain Zn Concentration

Abstract: An effective solution to global human zinc (Zn) deficiency is Zn biofortification of staple food crops, which has been hindered by the low available Zn in calcareous soils worldwide. Many culturable soil microbes have been reported to increase Zn availability in the laboratory, while the status of these microbes in fields and whether there are unculturable Zn-mobilizing microbes remain unexplored. Here, we use the culture-independent metagenomic sequencing to investigate the rhizosphere microbiome of three hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…PR3) with 75% RDF (recommended dose of fertilizers) showed an improved level of Zn uptake (323.8 g/h) in wheat (191). Recently, the metagenomics-based study revealed the existence of potential Zn-mobilizing species, particularly Massilia and Pseudomonas sp., that could form a functional community in increasing Zn concentration in grains of wheat varieties (192). More recent studies that decipher the microbial-assisted improvement in the plant yield and Zn content of crop plants are listed in Table 2.…”
Section: Scenario Of Microbial Inoculants In Zn Exemplification In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…PR3) with 75% RDF (recommended dose of fertilizers) showed an improved level of Zn uptake (323.8 g/h) in wheat (191). Recently, the metagenomics-based study revealed the existence of potential Zn-mobilizing species, particularly Massilia and Pseudomonas sp., that could form a functional community in increasing Zn concentration in grains of wheat varieties (192). More recent studies that decipher the microbial-assisted improvement in the plant yield and Zn content of crop plants are listed in Table 2.…”
Section: Scenario Of Microbial Inoculants In Zn Exemplification In Plantsmentioning
confidence: 99%
“…Molecular approaches of culture-independent methods for determining the functional gene or microbial diversity in soil have been developed considerably in the recent past. Metagenomics also offers new perspectives to identify the existence and abundance of certain microorganisms or functional genes specific for soil Zn mobilization or increasing root Zn uptake, mainly the synthesis of OAs and siderophores (192).…”
Section: Rhizobium Radiobactermentioning
confidence: 99%
“…When comparing the presence of Zn-mobilizing species such as Adhaeribacter , Janthinobacterium , Massilia , and Pseudomonas in rhizospheric and bulk soil of wheat, it was observed that the relative abundance was higher in the rhizosphere that could articulate the local community structure to improve the plant growth by mobilizing nutrients ( Wang et al., 2021 ). Acinetobacter was highly prominent, while Pantoea , Pseudomonas , and Paracoccus were also detected from the endosperm of T. aestivum cv.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of these studies advise reducing the spreading of ARG from amendment onto the lettuce leaf surface as this may influence human health negatively. Many other scientific questions can be tackled using metagenomics, such as Zn availability in grains for biofortification ( Wang et al, 2021 ), or the detection of foodborne pathogens in production chains ( Yang et al, 2016 ).…”
Section: Meta-omics Approaches: Guidelines For and Applications To Th...mentioning
confidence: 99%